Perception of Problem Based Learning by Undergraduate Dental Students in Basic Medical Science - Paudel, Sabita; Subedi, Nuwadatta; Sapkota, Subash; Shrestha, Bijayata; Shrestha, Sanjeeb (Journal of Nepal Health Research Council, 2021)
Background: Problem based learning is self-directed form of learning. Problem of Diabetes Mellitus was chosen. The objective was to evaluate perception of students towards Problem based learning and test their understanding. Methods: A descriptive study was conducted from November 2019 till October 2020. An online Problem based learning session of a week was conducted to second-year Bachelors of Dental Surgery students using online applications. Tutors facilitated students in a group of five to six each. Pre-post testing of evaluation questions was done. At end of session, feedback of students on Problem based learning and tutor of Problem based learning were received with ‘Dolmans and Schmidt’ and ‘Dolmans and Ginns’ questionnaire. Results: There was increase in correct response in nine out of 12 evaluation questions. Most students agreed to influence of discussion, content tested, course objectives, lectures, tutor and reference literature. The students agreed that tutors facilitated active, self-directed, contextual and collaborative learning. Conclusions: The influence of discussion among participants, content tested, course objectives, reference literature during the Problem based learning session were agreed upon by majority of the students. The tutors’ role was accepted by participants in terms of stimulation to self-directed, active, collaborative and contextual learning. Keywords: Diabetes mellitus; problem based learning; tutor